The system of reference in classic and ergonomic anthropometry - Batogowska, Anna; Słowikowski, Jerzy (Anthropological Review, 1979)
For the purpose of realizing whether it is possible to conduct a research and what kind of research according to the principles of classic anthropometry the system of reference applied in the classic and ergonomic anthropometry has been discussed. The authors have stressed and tried to prove that there is possible to obtain only a small number of information useful for designers and constructors when the research is carried on with the aid of the classic system of reference applied in anthropometry. The necessity has bean presented of connecting the discipline of the classic way thinking utilized in anthropometry with that applied in ergonomics as it makes possible to attain with the aid of ergonomics the new practical aims defined by the evolution of technology. The problems of including anthropometry in the technology have been also discussed as well as the problem of taking into consideration in the methodics of the anthropometric rescarch new situations resulting from increasing complexity of machines. The new term has been introduced: „Ergonomical anthropometry”, for a system of measured features, system of reference, methods and technics of measurements different from classic anthropometry.